Method for constructing micro-nano structure on glass surface by using NaCl as template

The micro-nano structure is constructed by combining NaCl particles with the glass surface, which solves the problems of poor mechanical durability and environmental pollution of existing superhydrophobic materials, and realizes the wear-resistant and corrosion-resistant superhydrophobic glass surface, which reduces processing costs and improves the process environmental protection.

CN119161108APending Publication Date: 2024-12-20NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411305917.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The mechanical durability of existing superhydrophobic materials is poor, and the traditional construction methods are expensive, have high technical requirements and may cause environmental pollution, making it difficult to achieve glass surface treatment that is both superhydrophobic and wear-resistant.

Method used

Using NaCl particles as templates, the micro-nano structure is constructed by combining with the glass surface, and the characteristics of the glass itself are used to achieve wear-resistant and corrosion-resistant superhydrophobic surfaces. A simple process and low-cost chemical reagents are used to avoid strong corrosion. Use of chemicals.

Benefits of technology

It realizes superhydrophobic effect with superior mechanical durability on the glass surface, reduces processing costs, and is environmentally friendly in the process, avoids environmental pollution, and has a highly designed micro-nano structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161108A_ABST
    Figure CN119161108A_ABST
Patent Text Reader

Abstract

The invention discloses a method for constructing a micro-nano structure on a glass surface by using NaCl as a template, and relates to the technical field of surface processing, and the process comprises the following steps: adding NaCl particles ground to a certain particle size into an organic carrier provided by the invention, stirring to obtain NaCl slurry, then removing dust and oil stains on the glass surface by using alcohol and deionized water, and finally, adding the NaCl particles into the organic carrier to obtain the micro-nano structure on the glass surface. The pretreated glass surface is coated with NaCl slurry, high-temperature calcination is performed after drying, NaCl is removed through ultrasonic cleaning after cooling, and the surface with the micro-nano structure is obtained. According to the construction method of the micro-nano structure, corrosive reagents such as hydrofluoric acid and sodium hydroxide which are harmful to the environment and human bodies do not need to be used, instruments such as lasers which are high in cost are not needed either, only the NaCl particles which are low in cost are used, and the micro-nano structure can be constructed on the surface of the glass under the more environment-friendly, convenient and economical conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of surface processing, and in particular to a method for constructing a micro-nano structure on a glass surface by using NaCl as a template. Background Art

[0002] Micro-nano structures refer to structures with sizes at the micron and nanometer levels. These structures have unique physical and chemical properties. Constructing micro-nano structures can make the material surface have properties such as super-hydrophobicity, super-hydrophilicity, wear resistance and friction reduction, and light trapping.

[0003] Nowadays, the application of superhydrophobic materials has involved all aspects of our lives. Its anti-corrosion, antibacterial, antifouling and self-cleaning properties have received widespread attention from researchers. Usually, a surface with a static water contact angle (WCA) greater than 150° and a rolling angle (WRA) less than 10° is defined as a superhydrophobic surface. Combining the Wenzel model and the Cassie model, the static water contact angle of a solid is related to the surface energy and surface roughness of the solid. With the promotion of the Wenzel model and the Cassie model and the continuous improvement of the superhydrophobic theory, scholars have summarized the two major factors necessary for the preparation of superhydrophobic surfaces, namely reducing the surface energy of the solid surface and constructing a rough microstructure on the solid surface.

[0004] Common methods for constructing super-hydrophobic surfaces include spraying, dipping, etc., in which low surface energy materials mixed with micro-nano particles are coated on a substrate. This method achieves super-hydrophobicity by utilizing the size and shape of micro-nano particles such as SiO2, Al2O3, and carbon nanotubes. The roughness of the surface. The advantages of this method are simple operation and fast preparation, but poor mechanical durability, poor friction resistance of the coating, and poor bonding performance; another method is to achieve super-hydrophobicity by coating a low surface energy material after surface roughening. Common methods for surface roughening include plasma treatment, 3D printing, laser etching, acid-base etching, etc. The coating constructed by this method has good mechanical durability, but it is expensive, has high technical requirements, and can cause environmental pollution. For example, the substrate is roughened by micro-nano particles of dipping and spraying methods, and then coated with low surface energy materials, a super-hydrophobic coating with good mechanical durability can be obtained by a simple, fast and green method. Summary of the invention

[0005] The purpose of the present invention is to address the shortcomings of the above-mentioned background technology and provide a method for constructing a micro-nano structure on a glass surface using NaCl as a template. A super-hydrophobic substrate or intermediate layer with superior mechanical durability is prepared by combining NaCl particles with wear-resistant and corrosion-resistant glass. The surface of the obtained micro-nano structure has excellent surface morphology and roughness, and the materials used in the preparation process are simple and the operation is convenient.

[0006] The present invention adopts the following technical solutions to achieve the above-mentioned purpose:

[0007] A method for constructing a micro-nano structure on a glass surface using NaCl as a template, the method specifically comprising the following steps:

[0008] Step S1: preparing an organic carrier, stirring an organic solvent, a thixotropic agent and a thickener in a water bath for a certain period of time to obtain an organic carrier;

[0009] Step S2: preparing NaCl slurry, adding NaCl particles ground to a certain particle size into an organic carrier, and stirring to obtain NaCl slurry;

[0010] Step S3: pretreatment to remove dust and oil stains on the glass surface;

[0011] Step S4: coating, coating the NaCl slurry prepared in step S2 on the glass surface pretreated in step S3, and drying;

[0012] Step S5: keeping the temperature, moving the glass surface coated with NaCl slurry in step S4 into a muffle furnace, heating it, and calcining it;

[0013] Step S6: Ultrasonic cleaning: ultrasonically cleaning the glass surface calcined in step S5 to remove NaCl, and drying to obtain a glass surface with a micro-nano structure.

[0014] Preferably, in step S1, the organic carrier is composed of an organic solvent, a thixotropic agent and a thickener, the organic solvent includes turpentine alcohol, dibutyl phthalate, and diethylene glycol butyl ether acetate, the thixotropic agent is castor oil, and the thickener is ethyl cellulose. The mass ratio of the organic solvent, the thixotropic agent and the thickener is x:y:z; wherein the range of x is 80-90, the range of y is 2-5, and the range of z is 5-18.

[0015] Preferably, in step S1, the preparation temperature of the organic carrier is 70-90° C., and the stirring time is 20-40 min.

[0016] Preferably, in step S1, the particle size of the NaCl particles after grinding and sieving is 1 μm-250 μm.

[0017] Preferably, in step S2, the mass ratio of NaCl particles to organic carrier in the slurry is m:n; wherein m is in the range of 1-6, and n is in the range of 4-9.

[0018] Preferably, in step S2, the stirring time is 3-5 hours.

[0019] Preferably, in step S3, the pretreatment is to use anhydrous ethanol and deionized water to clean the glass in sequence to remove stains attached to the glass surface.

[0020] Preferably, in step S4, the coating method used is steel screen printing, and the slurry coating amount is 0.01-0.06g.

[0021] Preferably, in step S5, the heating rate is 5-10°C / min, the calcination temperature is 400-1600°C, and the calcination time is 15-120min.

[0022] Preferably, in step S6, the ultrasonic cleaning time is 10-30 min, and the cleaning temperature is 20-60°C.

[0023] Compared with the prior art, the present invention adopts the above technical solution to have the following beneficial effects:

[0024] 1. The present invention provides a method for constructing a micro-nano structure on a glass surface using NaCl as a template. The micro-nano structure is constructed by etching the glass surface with NaCl particles. With the help of the characteristics of the glass itself, the constructed micro-nano structure has excellent friction resistance and corrosion resistance.

[0025] 2. The present invention provides a method for constructing a micro-nano structure on a glass surface using NaCl as a template. The micro-nano structure is constructed on the glass surface by etching the glass surface with NaCl particles. This is a physical construction method that does not require the use of highly corrosive chemicals, reduces harm to the environment and human body, and is a more environmentally friendly processing method.

[0026] 3. The present invention provides a method for constructing a micro-nano structure on a glass surface using NaCl as a template, which can realize the construction of a micro-nano structure in a specified area. Compared with the traditional corrosive construction of a micro-nano structure, the method has strong designability;

[0027] 4. The present invention provides a method for constructing a micro-nano structure on a glass surface using NaCl as a template, using NaCl particles to replace external processing forces such as lasers, and the chemical reagents used are inexpensive, convenient and easy to obtain, which greatly reduces the cost of constructing the micro-nano structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1 This is a SEM image of the untreated surface of the low-melting-point glass FD66 self-fired glass of the present invention at a scale of 50 μm;

[0030] Figure 2This is a SEM image of the surface at a scale of 100 μm after calcination but without ultrasonic cleaning to remove NaCl according to the present invention;

[0031] Figure 3 This is a SEM image of the glass surface micro-nano structure prepared in Example 1 of the present invention at a scale of 50 μm;

[0032] Figure 4 This is a SEM image of the glass surface micro-nano structure prepared in Example 2 of the present invention at a scale of 50 μm;

[0033] Figure 5 This is a SEM image of the glass surface micro-nano structure prepared in Example 3 of the present invention at a scale of 500 μm;

[0034] Figure 6 This is a SEM image of the glass surface micro-nano structure prepared in Example 3 of the present invention at a scale of 50 μm;

[0035] Figure 7 This is a SEM image of the glass surface micro-nano structure prepared in Example 4 of the present invention at a scale of 500 μm;

[0036] Figure 8 This is a SEM image of the glass surface micro-nano structure prepared in Example 4 of the present invention at a scale of 50 μm;

[0037] Fig. 9 This is a SEM image of the glass surface micro-nano structure prepared in Comparative Example 1 of the present invention at a scale of 50 μm;

[0038] Fig.10 This is a SEM image of the glass surface micro-nano structure prepared in Comparative Example 2 of the present invention at a scale of 50 μm;

[0039] Fig.11 This is a SEM image of the glass surface micro-nano structure prepared in Comparative Example 3 of the present invention at a scale of 500 μm;

[0040] Fig.12 This is a SEM image of the glass surface micro-nano structure prepared in Comparative Example 3 of the present invention at a scale of 50 μm;

[0041] Fig.13 This is a SEM image of the glass surface micro-nano structure prepared in Comparative Example 4 of the present invention at a scale of 500 μm;

[0042] Fig.14 This is a SEM image of the glass surface micro-nano structure prepared in Comparative Example 4 of the present invention at a scale of 50 μm. DETAILED DESCRIPTION

[0043] In order to more clearly describe the ideas, technical solutions and advantages of the present invention, the specific implementation methods are illustrated by examples and drawings. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] In the following description, for the purpose of illustration rather than limitation, specific details such as specific system structures and technologies are provided to provide a thorough understanding of the embodiments of the present invention. However, it should be clear to those skilled in the art that the present invention may also be implemented in other embodiments without these specific details.

[0045] Example 1

[0046] Step S1-1: preparing an organic carrier, taking 50 g of turpentine alcohol, 35 g of diethylene glycol butyl ether acetate, 5 g of dibutyl phthalate, 2 g of castor oil, and 15 g of ethyl cellulose, heating in a water bath at 90° C. with stirring for 30 min to obtain an organic carrier;

[0047] Step S1-2: preparing NaCl slurry, adding NaCl particles with D90=48 μm into an organic carrier, wherein m(NaCl):m(organic carrier)=1:9, and stirring for 4 h to obtain NaCl slurry;

[0048] Step S1-3: pretreatment, using anhydrous ethanol and deionized water to clean the glass in turn to remove dust and oil on the glass surface; the glass used in this experiment is low-melting-point glass powder FD66 self-burning glass, the main elements are silicon aluminum oxide, and the initial melting temperature is 500°C;

[0049] Step S1-4: coating, the NaCl slurry prepared in step S1-2 is uniformly coated on the glass surface pretreated in step S1-3 by steel screen printing, the coating amount is 0.04 g, and then dried;

[0050] Step S1-5: heat preservation, move the glass surface coated in step S1-4 into a muffle furnace, heat it at 350°C for 30 minutes to remove binder and heat it up, and heat it at 600°C for 20 minutes to calcine;

[0051] Step S1-6: Ultrasonic cleaning: the glass surface calcined in step S1-5 is ultrasonically cleaned at 45° C. for 15 minutes to remove NaCl, and then dried to obtain a glass surface with a micro-nano structure.

[0052] Example 2

[0053] Step S2-1: preparing an organic carrier, taking 50 g of turpentine alcohol, 35 g of diethylene glycol butyl ether acetate, 5 g of dibutyl phthalate, 2 g of castor oil, and 15 g of ethyl cellulose, heating in a water bath at 90° C. with stirring for 30 min to obtain an organic carrier;

[0054] Step S2-2: preparing NaCl slurry, adding NaCl particles with D90=48 μm into an organic carrier, wherein m(NaCl):m(organic carrier)=1:9, and stirring for 4 h to obtain NaCl slurry;

[0055] Step S2-3: Pretreatment, using anhydrous ethanol and deionized water to clean the glass in turn to remove dust and oil stains on the glass surface; the glass used in this experiment is low-melting-point glass powder FD66 self-burning glass, the main elements are silicon aluminum oxide, and the initial melting temperature is 500°C;

[0056] Step S2-4: coating, the NaCl slurry prepared in step S2-2 is uniformly coated on the glass surface pretreated in step S2-3 by steel screen printing, the coating amount is 0.04 g, and then dried;

[0057] Step S2-5: heat preservation, move the coated glass surface in step S2-4 into a muffle furnace, heat it at 350°C for 30 minutes to remove binder and heat it up, and heat it at 600°C for 15 minutes to calcine;

[0058] Step S2-6: Ultrasonic cleaning: the glass surface calcined in step S2-5 is ultrasonically cleaned at 45° C. for 15 minutes to remove NaCl, and then dried to obtain a glass surface with a micro-nano structure.

[0059] Example 3

[0060] Step S3-1: preparing an organic carrier, taking 50 g of turpentine alcohol, 35 g of diethylene glycol butyl ether acetate, 5 g of dibutyl phthalate, 2 g of castor oil, and 15 g of ethyl cellulose, heating in a water bath at 90° C. with stirring for 30 min to obtain an organic carrier;

[0061] Step S3-2: preparing NaCl slurry, adding NaCl particles with D90=48 μm and D90=74 μm into an organic carrier in a mass ratio of 1:1, wherein m(NaCl):m(organic carrier)=1:9, and stirring for 4 hours to obtain NaCl slurry;

[0062] Step S3-3: pretreatment, using anhydrous ethanol and deionized water to clean the glass in turn to remove dust and oil stains on the glass surface; the glass used in this experiment is low-melting-point glass powder FD66 self-burning glass, the main elements are silicon aluminum oxide, and the initial melting temperature is 500°C;

[0063] Step S3-4: coating, the NaCl slurry prepared in step S3-2 is uniformly coated on the glass surface pretreated in step S3-3 by steel screen printing, the coating amount is 0.04 g, and then dried;

[0064] Step S3-5: heat preservation, move the coated glass surface in step S3-4 into a muffle furnace, heat it at 350°C for 30 minutes to remove binder and heat it up, and heat it at 650°C for 15 minutes to calcine;

[0065] Step S3-6: Ultrasonic cleaning: the glass surface calcined in step S3-5 is ultrasonically cleaned at 45° C. for 15 minutes to remove NaCl, and then dried to obtain a glass surface with a micro-nano structure.

[0066] Example 4

[0067] Step S4-1: preparing an organic carrier, taking 50 g of turpentine alcohol, 35 g of diethylene glycol butyl ether acetate, 5 g of dibutyl phthalate, 2 g of castor oil, and 15 g of ethyl cellulose, heating in a water bath at 90° C. with stirring for 30 min to obtain an organic carrier;

[0068] Step S4-2: preparing NaCl slurry, adding NaCl particles with D90=180 μm, D90=74 μm and D90=48 μm into an organic carrier at a mass ratio of 2:1:1, wherein m(NaCl):m(organic carrier)=1:9, and stirring for 4 h to obtain NaCl slurry;

[0069] Step S4-3: Pretreatment, using anhydrous ethanol and deionized water to clean the glass in turn to remove dust and oil on the glass surface; the glass used in this experiment is low-melting-point glass powder FD66 self-burning glass, the main elements are silicon aluminum oxide, and the initial melting temperature is 500°C;

[0070] Step S4-4: coating, the NaCl slurry prepared in step S4-2 is uniformly coated on the glass surface pretreated in step S4-3 by steel screen printing, the coating amount is 0.04 g, and then dried;

[0071] Step S4-5: heat preservation, move the coated glass surface in step S4-4 into a muffle furnace, heat it at 350°C for 30 minutes to remove binder and heat it up, and heat it at 650°C for 15 minutes to calcine;

[0072] Step S4-6: Ultrasonic cleaning: the glass surface calcined in step S4-5 is ultrasonically cleaned at 45° C. for 15 minutes to remove NaCl, and then dried to obtain a glass surface with a micro-nano structure.

[0073] Comparative Example 1

[0074] The steps are basically the same as those in Example 1, except that "NaCl particles with D90=48μm are added to the organic carrier" in step S1-2 is replaced by "NaCl particles with D90=48μm and D90=74μm are added to the organic carrier in a mass ratio of 1:1".

[0075] Comparative Example 2

[0076] The steps are basically the same as those in Example 1, except that "calcination at 600°C for 20 min" in step S1-5 is replaced by "calcination at 600°C for 30 min".

[0077] Comparative Example 3

[0078] The steps are basically the same as those in Example 3, except that "calcining at 650°C for 15 min" in step S3-5 is replaced by "calcining at 620°C for 15 min".

[0079] Comparative Example 4

[0080] The steps are basically the same as those in Example 4, except that "the coating amount is 0.04 g" in step S4-4 is replaced by "the coating amount is 0.02 g".

[0081] Performance Testing

[0082] The micro-nano structure samples prepared in the above embodiments and comparative examples were subjected to a roughness test using a KC series laser spectral confocal microscope.

[0083] Table 1

[0084]

[0085] The morphology of the untreated glass surface, the surface coated with NaCl but not ultrasonically treated, and the micro-nano structures of the glass surfaces prepared in Examples 1-4 and Comparative Examples 1-4 were characterized. Figure 1-14 .

[0086] Depend on Figure 1-14 The results show that both the embodiments of the present invention and the comparative examples use NaCl particles to construct micro-nano structures on the glass surface. According to the process parameter analysis of the embodiments and the comparative examples, the size of the micro-nano structure, the roughness of the sample surface and other characteristics are related to parameters such as the particle size of the NaCl particles, the glass calcination temperature, the calcination insulation time and the coating amount.

[0087] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for constructing a micro-nano structure on a glass surface using NaCl as a template, characterized in that: The method specifically comprises the following steps: Step S1: preparing an organic carrier, stirring an organic solvent, a thixotropic agent and a thickener in a water bath for a certain period of time to obtain an organic carrier; Step S2: preparing NaCl slurry, adding NaCl particles ground to a certain particle size into an organic carrier, and stirring to obtain NaCl slurry; Step S3: pretreatment to remove dust and oil stains on the glass surface; Step S4: coating, coating the NaCl slurry prepared in step S2 on the glass surface pretreated in step S3, and drying; Step S5: keeping the temperature, moving the glass surface coated with NaCl slurry in step S4 into a muffle furnace, heating up, and calcining; Step S6: Ultrasonic cleaning: ultrasonically cleaning the glass surface calcined in step S5 to remove NaCl, and drying to obtain a glass surface with a micro-nano structure.

2. The method for constructing a micro-nano structure on a glass surface using NaCl as a template according to claim 1, characterized in that: In step S1, the organic carrier is composed of an organic solvent, a thixotropic agent and a thickener, the organic solvent includes turpentine alcohol, dibutyl phthalate, and diethylene glycol butyl ether acetate, the thixotropic agent is castor oil, and the thickener is ethyl cellulose. The mass ratio of the organic solvent, the thixotropic agent and the thickener is x:y:z; wherein the range of x is 80-90, the range of y is 2-5, and the range of z is 5-18.

3. The method for constructing a micro-nano structure on a glass surface using NaCl as a template according to claim 1, characterized in that: In step S1, the preparation temperature of the organic carrier is 70-90° C., and the stirring time is 20-40 min.

4. The method for constructing a micro-nano structure on a glass surface using NaCl as a template according to claim 1, characterized in that: In step S2, the NaCl particles are ground and sieved to have a particle size of 1 μm-250 μm.

5. The method for constructing a micro-nano structure on a glass surface using NaCl as a template according to claim 1, characterized in that: In step S2, the mass ratio of NaCl particles to organic carrier in the slurry is m:n, wherein m is in the range of 1-6 and n is in the range of 4-9.

6. The method for constructing a micro-nano structure on a glass surface using NaCl as a template according to claim 1, characterized in that: In step S2, the stirring time is 3-5 hours.

7. The method of constructing a micro-nano structure on a glass surface using NaCl as a template according to claim 1, characterized in that: In step S3, the pretreatment is to use anhydrous ethanol and deionized water to clean the glass in sequence to remove stains attached to the glass surface.

8. The method for constructing a micro-nano structure on a glass surface using NaCl as a template according to claim 1, characterized in that: In step S4, the coating method used is steel screen printing, and the slurry coating amount is 0.01-0.06g.

9. The method for constructing a micro-nano structure on a glass surface using NaCl as a template according to claim 1, characterized in that: In step S5, the heating rate is 5-10°C / min, the calcination temperature is 400-1600°C, and the calcination time is 15-120min.

10. The method of constructing a micro-nano structure on a glass surface using NaCl as a template according to claim 1, characterized in that: In step S6, the ultrasonic cleaning time is 10-30 minutes, and the cleaning temperature is 20-60°C.

Citation Information

Patent Citations

  • Microstructured glass substrates

    US20110209752A1